Pengaruh Penambahan Karagenan Terhadap Karakteristik Permen Jelly Rujak Mengkudu - Desy Melinia Sari, Ni Luh Putu; Ekawati, I Gusti Ayu; Ari Yusasrini, Ni Luh (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 4 (2023): Jurnal ITEPA, 2023)
Noni is a fruit that has many benefits and is also famous for its distinctive pungent odor. One way to reduce the odor of noni is to make it into a salad which can then be used as a base for jelly candy. Making noni salad jelly candy using carrageenan as a gel material. The purpose of this study was to determine the effect of the addition of carrageenan on the characteristic of noni salad jelly candy and the right amount of carrageenan to produce noni salad jelly candy with the best characteristics. The design used in this study was a completely randomized design (CRD) with the addition of carrageenan which consisted of 5 treatment levels, namely: 1%, 2%, 3%, 4% and 5%, each treatment was repeated 3 times to obtain 15 experimental units. The data were analyzed by analysis of variance and if the treatment had a significant effect (P<0.05) on the observed variables, then it was continued with Duncan's Multiple Range Test (DMRT). The results showed that the addition of carrageenan had a significant effect on water content, reduction sugar content, level of elasticity, color sensory, texture, aroma, taste, and overall acceptance of noni salad jelly candy. The treatment with the addition of 4% carrageenan produced noni salad jelly candy with the best characteristics, namely water content 18.75%, ash content 0.92%, reduction sugar content 30.82%, texture 18.06 N, brown color were liked, neutral aroma, taste were liked, chewy texture were liked, and overall acceptance were liked.